Policy styles and India’s national action plan on climate change (NAPCC) - Deshpande, Tanvi; Mukherji, Rahul; Sastry, Mekhala (Policy studies, 2023)
This article assesses India’s policy style, with respect to climate change particularly the launch of the National Action Plan on Climate Change (NAPCC). The NAPCC was India’s first significant climate policy document that demonstrates a paradigm shift from the “structural conflict” policy paradigm towards “embedded liberalism”. Policy ideas favouring “embedded liberalism” emerged from the Indian state were significant for the formulation of the NAPCC. The NAPCC was formulated due to a proactive and partially consensual policy style. The policymaking processes of “learning & puzzling” regarding a domestic climate policy involved relevant state and non-state actors and the policy idea was “powered” by the Prime Minister’s Office (PMO). This article explores interactions between state and non-state actors to find that the Indian government, in the context of the global aspirations of an emerging power faciliated and led the formulation of the NAPCC under an embedded liberal climate policy paradigm.
Gesehen am 27.11.2023
Ahead-of-print, 2023